The Role And Position Of Women In Islam According To Hanapi Agustin And Dewi Ratna In The Journal Of Gender Studies - Abdul Aziz Romdhoni (Penerbit Hellow Pustaka, 2024)
In the Islamic view, a woman has a very high position and has a huge influence on the lives of all mankind. The Al-Qur'an also explains that the role of a woman is very important and good as a mother, wife, sister, child or as a member of society. QS Ali Imran verse 195. Allah states that men and women have the same role. Where a husband is given the role of leader of the household, as well as protecting and providing for the family. Meanwhile, the wife plays the role of responsible household organizer led by the husband. Women have extraordinary duties and roles related to their position as mothers. Women as mothers in the Islamic view have a noble position, as the words of the Prophet Muhammad as narrated by Ahmad from al-Qudhâ'î read: